2012
DOI: 10.1371/journal.pone.0031888
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Barriers to Personal Health Record Use among Patients Attending a Safety-Net Clinic

Abstract: BackgroundPersonal health records (PHR) may improve patients' health by providing access to and context for health information. Among patients receiving care at a safety-net HIV/AIDS clinic, we examined the hypothesis that a mental health (MH) or substance use (SU) condition represents a barrier to engagement with web-based health information, as measured by consent to participate in a trial that provided access to personal (PHR) or general (non-PHR) health information portals and by completion of baseline stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…There may be several reasons for this, including differences in scheduling personnel for different clinics, patient access to the internet, computer literacy, and psychosocial factors. Computer illiteracy (Hilton et al, 2012; Simon et al, 2008) and the inability to access the internet at home (Simon et al, 2008) are associated with inability to engage in web-based health information. However, other research has shown that patients living in either suburban or urban areas were equally likely to access the internet, even though suburban residents were more likely to own a computer and urban residents had a higher odds of being uninsured (Bond et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be several reasons for this, including differences in scheduling personnel for different clinics, patient access to the internet, computer literacy, and psychosocial factors. Computer illiteracy (Hilton et al, 2012; Simon et al, 2008) and the inability to access the internet at home (Simon et al, 2008) are associated with inability to engage in web-based health information. However, other research has shown that patients living in either suburban or urban areas were equally likely to access the internet, even though suburban residents were more likely to own a computer and urban residents had a higher odds of being uninsured (Bond et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Household income cannot always predict internet use (Appleby-Tagoe et al, 2012; Bond et al, 2012; Simon et al, 2008). Research has shown that mental health issues and substance use have not been barriers to online health information either (Hilton et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…17 Mental health and substance abuse issues did not seem to affect a participants' ability to access information online 18 . In addition, innovative methods of delivering ePHR though an Apple iPod device were accepted by participants and resulted in greater self-efficacy for self-care.…”
Section: Discussionmentioning
confidence: 96%
“…Fostering patient use of technology for self-management of chronic diseases could result in decreased demand on clinicians in primary care environments. Several studies have shown the acceptability of utilizing ePHRs in HIV primary care clinics (16, 17). In these studies, young Caucasian men found the ePHR to be a useful tool in managing their HIV care, but the studies were not able to enroll a more diverse racial or gender sample.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, young Caucasian men found the ePHR to be a useful tool in managing their HIV care, but the studies were not able to enroll a more diverse racial or gender sample. Investigators of another study found that substance use itself was not a barrier to completing online health related surveys through an ePHR in an urban HIV clinic sample (16). A computer-based SBIRT intervention could be a feasible method for addressing substance use in an HIV primary care clinic.…”
Section: Introductionmentioning
confidence: 99%